Medical Educators' conceptions about Generic Competences in Argentina: Contributions for consensus building - Roberta Inés Ladenheim; Cecilia Inés Hernández (Universidad de Deusto, 2018)
Healthcare professionals' education is evolving to meet people's needs towards a more comprehensive, collaborative and interdisciplinary training. In medical education in Argentina, in the context of international discussions around competence-based education (CBE), competence frameworks are being developed for undergraduate and postgraduate education, constituting agreed criteria that lead to the design of training programs and work as key tools to ensure educational quality. The Tuning Project and other international frameworks account for this process towards a common definition of standards beyond geographic and disciplinary boundaries. Generic competences (GCs) have acquired increased relevance in CBE discussions, whereas in medical education they involve key skills for patient safety - yet clarity in their implementation still has to be accomplished. In competence-based medical education (CBME), some changes are being hindered by the absence of a common language as well as diverging ideologies and theories. The purpose of this work was to explore conceptions and the terms used when referring to GCs by people in charge of educational planning and design of Human Resources (HR) training policies in Argentina. A qualitative informants from different levels and fields in medical education. Interviews were conducted by one interviewer and analysed by two independent researchers. Results showed that medical educational planners have different conceptions regarding GCs and fail to share a common language to enunciate them. They acknowledge their relevance for patient safety and agree with the notion that, at this time of educational transformation, it would be useful to enunciate them separately from specific competences, although they realise that this involves potential risks in curricular design. From all terms used in this regard, "generic competence" was identified as a contradiction in itself. Consensus on denomination, meaning and visibility in curricula is mandatory. Received: 26 April 2018 Accepted: 18 May 2018 Published online: 31 May 2018